Synthesis of barium titanate-barium magnesium niobate solid solution by a mixed-oxide method - R. Roongtao (2018)
In the present study, the phase formation characteristics of the (1-x)BaTiO 3-xBa(Mg 1/3Nb 2/3)O 3 (or (1-x)BT-xBMN) system were examined as a function of processing conditions. Various preparation techniques and processing parameters are investigated in all samples. Phase formation and microstructural evolution are examined via X-ray diffraction (XRD) and scanning electron microscopy (SEM), respectively. From the results, it can be seen that complete solid solutions in the BT-BMN system was obtained. The optimum calcination temperature of the powder in this system increases with increasing BMN content. Additionally, the average particle size also increases with increasing BMN content. The larger particle size of BT-BMN powders may relate to the higher optimum calcination temperature for each composition.